An Investigation into the Pragmatic Competence of the Front-Office Trainees of Valombola Vocational Training Centre - Fredrick MacGyver Nghilinganye; Haileleul Zeleke Woldemariam (Faculty of Education and Teacher Training of UIN Palopo, 2023)
This study aimed to analyze the front-office trainees' pragmatic competence at Valombola VTC. The trainees were tested on their ability to formulate and implement strategies for requests, their politeness principles in the speech acts of refusal and apologetic responses, and the factors that impact their pragmatic competence. Fifteen out of thirty (2022) front-office trainees enrolled in the Hospitality Department's program were chosen for the study using a systematic random sampling method. A Written Discourse Completion Task (WDCT) and a questionnaire were utilized as data collection devices. Qualitative and quantitative analyses were conducted on the data about the students' pragmatic abilities. According to the study's results, the trainees' pragmatic competence was a dismal 30% when it came to the verbal act of refusing. It can be concluded that the trainees at the front desk lacked the pragmatic competence necessary to effectively respond to requests, offer apologies, and employ a refusal approach. Taking into account the outcomes of the three speech acts of asking, apologizing, and refusing, their pragmatic competence was found to be fairly low. This is in line with their preference for using their vernacular language when interacting with others, as shown even in the questionnaire. Furthermore, the results show that trainees employ various aggressive apologetic methods and reaction styles when asked to apologize. Finally, the results show that pragmatic competence is affected by several underlying issues, such as a lack of education, a low level of everyday activities involving English, and the misunderstanding of pragmatic implicature. Finally, the TVET sector as a whole and front-desk trainees in particular were advised to take English for Specific Purposes with an emphasis on pragmatic skills.